Keterkaitan Belanja Pemerintah terhadap PDRB Perkapita Kabupaten/Kota di Sulawesi Tenggara - Syuhada, La Ode Muhammad Tamzil; Rindayati, Wiwiek; Juanda, Bambang (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2023)
The issuance of Law No. 1 of 2022 as a complement to Law No. 23 of 2004 concerning financial relations between the central and regional governments. Fiscal transfer policies are becoming more selective in seeing local needs. However, this needs to be supported by good fiscal management in the regions to carry out development activities that have an impact on increasing income that is more evenly distributed between regions and communities. One of the important instruments of fiscal decentralization is the management of government spending. Therefore, the purpose of this study is to examine the relationship between government spending and per capita income in Southeast Sulawesi. The units of observation analyzed are gross regional domestic product per capita in the previous year, personnel expenditures, goods and services expenditures, capital expenditures, HDI, district and city dummy variables. The model approach in the calculation is panel data regression analysis from 2016-2020. Based on the test results, the probability (F-statistics) is obtained, the equation of income per capita the Hausman test > 0.05, then the random effect model (REM) equation is the best model choice. The results of the analysis show all independent variables have a strong relationship with the dependent variable in the model which is shown by an R-square of 0.982. Variables that show significant effect on the increase in percapita income are (???????(?−1)), goods and services expenditure, capital expenditure and HDI, while personnel expenditure has a negative effect on per capita income for both districts and cities in Southeast Sulawesi Province.